(untitled) (Journal of the College of Basic Education, 2022)
Human thought is a thought of sequences, in the sense that it emerges from the accumulation of knowledge, and knowledge is the result of multiple and diverse moments in human life. It has its procedures and controls the production of texts and their continuous reproductions, so there is no longer a text that establishes itself by itself, that is, every textuality is a textual overlap.